PERBEDAAN KUALITAS HIDUP YANG BERHUBUNGAN DENGAN GANGGUAN PENGLIHATAN PADA PENDERITA NON PROLIFERATIVE DIABETIC RETINOPATHY DAN PROLIFERATIVE DIABETIC RETINOPATHY - , Guntur Susetyo, Prof. dr. Suhardjo, SU, SpM (K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Diabetic retinopathy is the most common eye-related complications of diabetic patients affecting their quality of life due to decreased visual function. This vision impairment in diabetic retinopathy may occur in all stages of diabetic retinopathy including non-proliferative (NPDR) and proliferative diabetic retinopathy (PDR). The Objective of this study was compared the quality of life in NPDR and PDR patients with decreased visual function. This was a cross-sectional study of patients with DR aged 30 â 70 years, having the minimum level of education of junior high school. A total of 70 persons were categorized into two groups: NPDR (35 persons) and PDR (35 persons). A structured interview was performed to obtained basic personal data including age, gender, level of education, occupation, duration of diabetes, medications, highest level of blood glucose, and binocular vision. Measurement of quality of life was included in the interview using NEI VFQ-25, covering all aspects: general health, general vision, ocular pain, near and distance activities, social functioning, mental health, role difficulties, dependency, driving, color vision, and peripheral vision. Results, compared to group with PDR, there were no differences in age, gender, level of education, occupation, duration of diabetes, and medication used in NPDR group. The highes glucose level and binocular vision of persons with PDR were statistically different compared to NPDR (p-values<0.05). Related to quality of life, the median score of near (75 NPDR vs. 50 PDR) and distance vision (91.7 vs. 58.3), social function (100 vs. 100), role difficulties (50 vs. 37.5), dependency (75 vs. 41.5), driving (75 vs. 0), color vision (100 vs. 100) and peripheral vision (100 vs. 100) in NPDR were statistically higher than PDR (all pvalues >0.05). Conclusion, the quality of life of patients with NPDR was better than those with PDR in relation to near and distance vision, social function, role difficulties, dependency, driving, color vision and peripheral vision.